2005
DOI: 10.1007/s00216-005-3237-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ultrasound-assisted extraction of cadmium from legumes and dried fruit samples coupled with on-line preconcentration-flame atomic absorption spectrometry

Abstract: Cadmium was continuously extracted with diluted nitric acid from legumes and dried fruit samples using a simple, rapid and continuous ultrasound-assisted extraction system. A minicolumn packed with a chelating resin (Chelite P, with aminomethylphosphoric acid groups) was placed between the extraction unit and the detector for cadmium preconcentration. The cadmium content in the acid extract was retained into the minicolumn, and elution was carried out with hydrochloric acid, with this trace metal continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…Ca is an essential mineral in the formation and maintenance of bones and teeth. This mineral is also involved in the transport of cellular membranes, the activation or release of enzymes, muscle contractions, and the transmission of nerve impulses (regulating the heartbeat) (Yebra & Cancela, 2005 (Ekholm et al, 2007) had higher levels of this mineral compared with those of the fruit samples examined in the present study.…”
Section: Minerals Analysis By Usn-icp-oesmentioning
confidence: 52%
“…Ca is an essential mineral in the formation and maintenance of bones and teeth. This mineral is also involved in the transport of cellular membranes, the activation or release of enzymes, muscle contractions, and the transmission of nerve impulses (regulating the heartbeat) (Yebra & Cancela, 2005 (Ekholm et al, 2007) had higher levels of this mineral compared with those of the fruit samples examined in the present study.…”
Section: Minerals Analysis By Usn-icp-oesmentioning
confidence: 52%
“…Many different studies and methods for heavy metal determination in different food stuffs have been reported in the literature including dry, wet and microwave digestion methods to investigate heavy metal levels in cheese, fruits, fruit juices, vegetables, sweets, chocolates, honey, snacks, appetizers, etc. (Soylak et al 2006;Radwan and Salama 2006;Zahoor et al 2003;Yebra and Cancela 2005;Nascentes et al 2004;Saracoglu et al 2004). Sweets including chewing gums and candies are not exactly a food, but it is especially consumed by children and pregnant woman with ingesting or chewing by teeth in mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies regarding the optimization of ultrasound assisted extraction for the on line determination of cadmium from legumes and dried fruit samples were proposed by Yebra et al [17,18]. In these papers, Cd was continuously extracted with diluted acid using a continuous ultrasoundassisted extraction system (CUES).…”
Section: Food Analysismentioning
confidence: 99%
“…In the last years chemometric approaches have been applied also for optimization of analytical methods based on the use of atomic spectroscopic techniques in the environmental [1][2][3][4][5][6][7][8][9][10] and food area [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Atomic Absorption Spectroscopy and Inductively Coupled Plasmmentioning
confidence: 99%